Analisis Kritis: Impelentasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Pendidikan Anak Usia Dini - Wulan Tini (Jurnal El-Audi, 2024)
The implementation of the Pancasila Student Profile Strengthening Project (P5) at the Early Childhood Education (PAUD) level within the Independent Curriculum was originally designed to foster children's character through a liberating approach. However, in practice, this paradigm shift has created epistemological and methodological conflicts for teachers in the field. This study aims to conduct a critical analysis of the implementation of P5 at the PAUD level, with a specific focus on pedagogical readiness, structural workload, and teachers' stuttering in translating the abstract values of Pancasila into child-friendly stimulation. Using a qualitative approach with critical case studies, data were collected from several PAUD units through in-depth interviews with teachers, participatory observation of the project process, and critical analysis of teaching module documents compiled independently by teachers. The results reveal the phenomenon of "curriculum formalism," where teachers are trapped in administrative performativity and product orientation (output) for the sake of documentation fulfillment, rather than prioritizing child agency and process-oriented reflection. The imbalance in Pedagogical Content Knowledge (PCK) tends to lead teachers to adopt a rigid (teacher-centered) instructional role, reducing the meaning of P5 to merely a seasonal craft activity. This research shows that early childhood education (PAUD) teachers experience dual pressures between structural administrative burdens and the idealistic demands of the new curriculum without adequate conceptual guidance. The implications of this research urge the need for a deconstructive reconstruction of teacher training patterns and a reorientation of P5 policies to return to the fundamental principles of early childhood play.